Above-ground and needle biomass models on a fast-growing pine plantation in Oaxaca - Rodríguez-Ortiz, Gerardo; De Los Santos-Posadas, Héctor M.; González-Hernández, Víctor A.; Aldrete, Arnulfo; Gómez-Guerrero, Armando; Fierros-González, Aurelio M. (Instituto de Ecología, A.C., 2016)
A forest tree health can be accurately assessed by evaluating foliage biomass; even when it represents only 4% to 6% of the total tree biomass, it is the main driver of every major physiological processes. This research was mainly focused on estimating accurately needle biomass at branch and tree level on fast growing trees of Pinus patula Schl. et Cham. Needle biomass per branch was estimated with a linear model, which used live branch basal area, live branch height, and crown section like independent variables.Above ground components were estimated with determination coefficients of 0,86, 0,92 and 0,88 for wood with bark, branches and needles. For the wood with bark model, diameter at breast height(DBH) and total tree height (HT) were used in a linear structure; total branch biomass was fitted with a non-linear model, using live crown diameter (LCD) and crown area (CA) while total needle biomass used LCD and HT on a non-linear model. The aboveground total biomass per tree was estimated with R2 = 0.87, using DBH and HT. At 14 years old, biomass partition was estimated to be 92,9%, 4,7% and 2,4% for wood with bark, branches and needles, respectively.